2009
DOI: 10.1007/s00221-009-1969-0
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary action and causality in temporal binding

Abstract: Previous studies have documented temporal attraction in perceived times of actions and their effects. While some authors argue that voluntary action is a necessary condition for this phenomenon, others claim that the causal relationship between action and effect is the crucial ingredient. In the present study, we investigate voluntary action and causality as the necessary and sufficient conditions for temporal binding. We used a variation of the launching effect proposed by Michotte, in which participants cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 16 publications
10
43
0
Order By: Relevance
“…Although the combination of voluntary action and visual sensory feedback was the same between the two conditions, the binding effect only emerged when the action was active and the finger had some kind of contact with the keyboard. This result is consistent with a previous study that found the intentional binding only emerged when the action was voluntary and causally connected to sensory feedback (Cravo et al 2009). However, because this previous study did not investigate other actions, the importance of the combination of voluntary action and contact with the keyboard in the two actions could not be determined.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although the combination of voluntary action and visual sensory feedback was the same between the two conditions, the binding effect only emerged when the action was active and the finger had some kind of contact with the keyboard. This result is consistent with a previous study that found the intentional binding only emerged when the action was voluntary and causally connected to sensory feedback (Cravo et al 2009). However, because this previous study did not investigate other actions, the importance of the combination of voluntary action and contact with the keyboard in the two actions could not be determined.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, there was no difference in the reported time among the voluntary key-release, involuntary key-press, and involuntary key-release conditions. The temporal binding effect for a voluntary key-press supports the results of previous studies that found this voluntary action induced a robust compression effect (Buehner 2012; Haggard et al 2002;Engbert and Wohlschläger 2007;Engbert et al 2008;Cravo et al 2009;Humphreys and Buehner 2009;Moore et al 2013Moore et al , 2009Ebert and Wegner 2010;Caspar et al 2015). Moreover, different subjective estimations of time between key-press and keyrelease actions were also demonstrated here by comparing the voluntary/involuntary key-press and key-release actions (Zhao et al 2013(Zhao et al , 2014b.…”
Section: Discussionsupporting
confidence: 90%
“…3C). The necessity of path 1 is clear from previous results (12,14), showing that intentional binding does not occur for involuntary movements.…”
Section: Exp 1: Involuntary Movementmentioning
confidence: 52%
“…This shift is compared with a baseline condition containing only a tone and no action. Importantly, involuntary movements are not sufficient to cause perceptual shifts of the tone, and a volitional signal appears necessary (12)(13)(14). A further control group of participants also judged the time of the tone following an involuntary movement, but had never experienced any association between involuntary and voluntary movement.…”
Section: Significancementioning
confidence: 99%
“…The sense of agency can be implicitly measured by the magnitude of apparent temporal compression between action and effect, the so-called intentional binding [23]. Strong intentional binding occurs with a strong sense of agency rating [7,24] and/or strong perception of causality [15,25,26]. We predicted that the additional-tones-induced reduction of grouping between action and its effect would result in a diminished sense of agency.…”
Section: Methodsmentioning
confidence: 99%